Origins of Aminergic Regulation of Behavior in Complex Insect Social Systems - Kamhi, J. Frances; Arganda, Sara; Moreau, Corrie S.; Traniello, James F. A. (Frontiers in Systems Neuroscience, 2017)
Neuromodulators are conserved across insect taxa, but how biogenic amines and their receptors in ancestral solitary forms have been co-opted to control behaviors in derived socially complex species is largely unknown. Here we explore patterns associated with the functions of octopamine, serotonin, and dopamine in solitary ancestral insects and their derived functions in eusocial ants, bees, wasps, and termites. Synthesizing current findings that reveal potential ancestral roles of monoamines in insects, we identify physiological processes and conserved behaviors under aminergic control, consider how biogenic amines may have evolved to modulate complex social behavior, and present focal research areas that warrant further study.